Pacific connections : the making of the U.S.-Canadian borderlands - Chang, Kornel S., 1976- (American crossroads ;, 2012)
In the late nineteenth century the borderlands between the United States, the British Empire in Canada, and the Asia-Pacific Rim emerged as a crossroads of the Pacific world. In Pacific Connections, Kornel Chang tells the dramatic stories of the laborers, merchants, smugglers, and activists who crossed these borders into the twentieth century, and the American and British empire-builders who countered them by hardening racial and national lines. But even as settler societies attempted to control the processes of imperial integration, their project fractured under its contradictions.